(untitled) - BURHAN NUDIN, IRKHAS (Jurnal Ilmu Manajemen (JIM), 2017)
It is very important for a company to pay attention to the level of career satisfaction, because it greatly affects the performance of employees. One of the important factors that can affect employee career satisfaction is work-family conflict. The purpose of this study was to examine the effect of work-family conflict towards career satisfaction is moderated by individual difference in PT Kereta Api Indonesia DAOP 8 Surabaya.This type of research was causality, with a quantitative approach. This study using stratified random sampling technique and analyzed using smart partial least square (smartPLS) analysis method. This study used a sample of 68 respondents drawn from employees of PT Kereta Api Indonesia DAOP 8 Surabaya. The scale of measurement in this study using a likert scale.The result showed that there was a negative and significant effect on work-family conflict on career satisfaction with the value 7,470. And the impact of work-family conflict on career satisfaction is moderated by individual difference with the value -2,278. Keywords: work-family conflict, career satisfaction, individual difference